Strategic Innovation and Bioeconomic Transformation of Nutmeg (Myristica fragrans) Agribusiness within the Dusung Agroforestry Framework of the Maluku Islands - Simanjorang, Tienni Mariana; Tiven, Nafly Comilo (Yayasan Cerdas Pedia Indonesia, 2026)
Nutmeg (Myristica fragrans) remains a strategically pivotal spice commodity, characterized by its profound historical, ecological, and economic significance within the Indonesian Maluku Archipelago. Despite Indonesia’s enduring comparative advantage in the global spice trade, the long-term sustainability and competitiveness of the nutmeg agribusiness are increasingly compromised by the socio-economic precariousness of smallholder producers and the structural inertia of conventional value chains. This research systematically evaluates the socio-economic profiles of nutmeg smallholders, analyzes the ecological-economic duality of the traditional dusung agroforestry system, and formulates strategic bioeconomic innovations to bolster global market positioning. Adopting a descriptive quantitative framework, primary data were elicited from a purposive sample of 75 smallholder farmers situated across primary production epicenters, including the Banda Islands, Leihitu, and West Leihitu sub-districts. The empirical results reveal a demographic skew toward an aging workforce (56% aged 41–60), characterized by extensive hereditary expertise but constrained by limited formal human capital (48% with only primary-level education). This educational deficit significantly inhibits the diffusion of modern technological innovations and complicates adherence to stringent international Sanitary and Phytosanitary (SPS) standards. Furthermore, while the dusung system demonstrates high ecological resilience and carbon sequestration potential, it remains ensnared in a low-productivity trap exacerbated by asymmetric market power and price discovery failures. The study concludes that a strategic pivot toward circular bioeconomic downstreaming encompassing volatile compound extraction, pharmaceutical-grade derivatives, and the integration of digital traceability is an absolute imperative. Such a transition is essential to elevate nutmeg cultivation from a subsistence-based legacy practice into a highly competitive, resilient, and sustainable global enterprise.